Counselling Needs of Out-Patients in University College Hospital Ibadan (UCH), Nigeria - Odebode, Aminat Adeola (NIU Journal of Humanities, 2018)
The inability of health personnel to meet certain needs of patients usually leads to patients’ dissatisfaction. This is actually and in no doubt, calls for proactive actions. This study therefore, investigated the counselling needs of out-patients in UCH Ibadan Nigeria. The study also examined the influence of level of education and religion on respondents’ views. Descriptive survey research design was adopted for the study. A total of 900 out-patients in UCH, Ibadan were selected using a three-stage sampling procedure which comprised simple random sampling, purposive and systematic random sampling techniques. The instrument used for data collection was a questionnaire entitled “Counselling Needs of Patients Questionnaire (CNPQ)’’. The validity of the questionnaire was established by three experts in the Departments of Counsellor Education. The reliability of the questionnaire was determined using split-half method and a correlation co-efficient of 0.86 was obtained. Analysis of Variance (ANOVA) and t-test statistical tools were used to analyze the formulated hypotheses at 0.05 alpha level. The findings showed that out-patients in UCH Ibadan needed counselling to handle negative thoughts relating to illness, cope with the state of being ill and disease management. The findings also revealed that there were significant differences in the counselling needs of out-patients in UCH Ibadan based on level of education and religion. The study concluded that health personnel generally should take courses in counselling to further enrich their knowledge and skills on meeting the counselling needs of patients.